Just the tonic! Legume biorefining for alcohol has the potential to reduce Europe's protein deficit and mitigate climate change. (September 2019) - Lienhardt, Theophile; Black, Kirsty; Saget, Sophie; Costa, Marcela Porto; Chadwick, David; Rees, Robert M.; Williams, Michael; Spillane, Charles; Iannetta, Pietro M.; Walker, Graeme; Styles, David
Abstract: Industrialised agriculture is heavily reliant upon synthetic nitrogen fertilisers and imported protein feeds, posing environmental and food security challenges. Increasing the cultivation of leguminous crops that biologically fix nitrogen and provide high protein feed and food could help to address these challenges. We report on the innovative use of an important leguminous crop, pea ( Pisum sativum L.), as a source of starch for alcohol (gin) production, yielding protein-rich animal feed as a co-product. We undertook life cycle assessment (LCA) to compare the environmental footprint of 1 L of packaged gin produced from either 1.43 kg of wheat grain or 2.42 kg of peas via fermentation and distillation into neutral spirit. Allocated environmental footprints for pea-gin were smaller than for wheat-gin across 12 of 14 environmental impact categories considered. Global warming, resource depletion, human toxicity, acidification and terrestrial eutrophication footprints were, respectively, 12%, 15%, 15%, 48% and 68% smaller, but direct land occupation was 112% greater, for pea-gin versus wheat-gin. Expansion of LCA boundaries indicated that co-products arising from the production of 1 L of wheat- or pea-gin could substitute up to 0.33 or 0.66 kg soybean animal feed, respectively, mitigating considerable greenhouse gas emissions associated with land clearing, cultivation, processing and transport of such feed. For pea-gin, this mitigation effect exceeds emissions from gin production and packaging, so that each L of bottled pea gin avoids 2.2 kg CO2 eq. There is great potential to scale the use of legume starches in production of alcoholic beverages and biofuels, reducing dependence on Latin American soybean associated with deforestation and offering considerable global mitigation potential in terms of climate change and nutrient leakage — estimated at circa 439 Tg CO2 eq. and 8.45 Tg N eq. annually. Graphical abstract: Unlabelled Image Highlights: Alcohol can be fermented from the starch of peas ( Pisum sativum L.) instead of wheat. Gin produced from peas had a smaller environmental footprint for 12 impact categories. Protein rich co-products of gin production substitute soybean and barley animal feed. Animal feed substitution more than offsets the carbon footprint of pea gin. Pea gin has a larger land footprint than wheat gin, depending on rotation effects.